SNOMED-CT as a standardized language system model for nursing: an integrative review - Carolina Giordani da Silva; Edwing Alberto Urrea Vega; Fernanda Peixoto Cordova; Flávia Aline Carneiro; Karina de Oliveira Azzolin; Lucas Henrique de Rosso; Murilo dos Santos Graeff; Patrícia Vasconcellos de Carvalho; Miriam de Abreu Almeida (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To describe the use of the Systematized Nomenclature of Medicine - Clinical Terms (SNOMED-CT) as a model for interoperability of the nursing terminology in the national and international contexts. Methods: This is an integrative literature review according to Cooper, which searched for articles in Portuguese, English and Spanish, published between September 2011 and November 2018 in the BVS, PubMed, SCOPUS, CINAHL, EMBASE, and Web of Science databases, ending in a sample of 15 articles. Results: The SNOMED-CT is a multi-professional nomenclature used by nursing in different care contexts, being associated with other standardized languages of the discipline, such as ICNP®, NANDA-I, and the Omaha System. Conclusion: This review has shown that the use of SNOMED- CT is incipient in the national context, justifying the need to develop studies aimed at mapping the interoperability of existing systems of standardized language, especially NANDA-I, ICNP and Omaha System, in order to adapt the implementation of SNOMED-CT.